Medidas morfométricas na avaliação de pesos e rendimentos corporais de Arapaima gigas - Luxinger, Acsa Otto (2017)
Aiming at improving the efficiency of aquaculture as a zootechnical activity, we seek nowadays for methods of evaluating animal productivity indices that are effective and allow their measurement without the need to slaughter the animals. It is in this context that track analysis arises, a method capable of making possible the knowledge of the direct and indirect effects that explanatory variables exert on a main variable, thus allowing to establish which strategy will be more efficient in the selection of animals with higher productive indexes. Thus, the objective of this study was to evaluate the morphometric variables directly associated with the pirarucu weights and body yields (Arapaima gigas). A total of 96 pirarucus were raised in captivity at the Federal University of Rondônia, Presidente Médici - RO, Brazil, with a average body weight of 8,62 ± 1,25 kg e 104 ± 4,7 cm in length. After being desensitized, they were euthanasied, weighed, and morphometric measured by total length (CT), standard (CP), head (CC), trunk (CTRO) and tail (CCAU); And frontal perimeters (PF), higher (PM) and tail (PCAU). Initially, the data were subjected to a multiple linear regression analysis using a stepwise procedure in the backward option so that possible multicollinearity effects were eliminated and independent variables were included in the Akaike criterion analysis (AIC). After checking the normality of the data using the Shapiro-wilk test, the correlations between the dependent and independent variables were calculated by Pearson's linear correlation coefficient, applying Student's t-test (α = 0.05) to assess their significance and later the correlation coefficients were deployed in direct and indirect effects. Most of the measurements and morphometric ratios showed a significant correlation with body weights and their component parts (carcass, head, blanket, leather, viscera and pimples). The PM morphometric measurement presented a greater direct and positive effect and was determinant for the variation of total weight and manta weight (component with higher commercial value). Measurements and morphometric ratios can be used with great precision to estimate the weights of the body components of pirarucu, with the exception of the weight of the spines. In addition, some morphometric measures could be used in breeding programs as an indirect selection measure for fish with better productive characteristics.